"Two-faced -isms: racism at work and how race discourse shapes classtalk and gendertalk.". (November 2015) - Embrick, David G.; Henricks, Kasey
Abstract: In this paper, we relied on a mixed-methods approach to examine the contextual fluidities and nuances of racial discourse in a southwestern baked-goods workplace. Specifically, we extend upon previous findings on how stereotypes and slurs are racially unequal in a workplace setting, in order to investigate what is uniquely racist about the deployment of stereotypes and slurs and how racism shapes gendered and classed dimensions of these terms. Further, we empirically demonstrate how gender and class can be constructed along lines of racial ideology at micro-levels of interaction. Our argument is that racetalk does not operate independently or in isolation from other discourses like gendertalk and classtalk. Instead, racist comments are often expressed alongside classist and sexist comments by people, who simultaneously occupy multiple racial, class, and gender locations. Highlights: That racist discourse is so salient that it partially determines gender and class. How language is differentially used in front-stage and back-stage contexts. Ways in which back- and front-stage contexts differ according to the actors who participate in them.